INVESTIGATING THE IMPACT OF A TRAINING PROGRAM TO EVALUATE THE QUALITY OF INDIVIDUAL PERFORMANCE OF ISLAMIC STUDIES STUDENTS AT SULTAN QABOOS UNIVERSITY: استقصاء أثر برنامج تدريبي لتقييم جودة الأداء الفردي لطلبة الدراسات الاسلامية بجامعة السلطان قابوس - Al Mazidi, Hamdan Salim Said; Yussuf, Ahmad; Rekan, Abd. Aziz (Online Journal of Islamic Management and Finance (OJIMF), 2024)
The current study focuses on investigating the Good Aim training program for students of the Islamic Studies students at Sultan Qaboos University, where the average evaluation continues through several stages that students go through as they activate this process, which are: planning the evaluation, collecting evidence, and issuing justice. Disposing of the judiciary and monitoring the effectiveness of the measures, as a technical study was conducted by 40 students from the Islamic Studies students in Sultan Qaboos. The study population was chosen from the bachelor’s level in its various academic departments. The age of the students ranged from 19 to 22 years. This sample was distributed equally into two groups, one an experimental sample and the other a random control sample. Since the aim of this study is to investigate the effect of a training program to evaluate the quality of Individual performance of students of the Islamic Studies students at Sultan Qaboos University. The students were trained on the evaluation stage processes according to a training program with specific time stages and objectives. The student in the experimental group was trained in these stages according to a number of 10 training sessions distributed over three training hours, including two practical hours and one theoretical hour, taking into account the timetable and the students’ academic circumstances in the college. To verify the effectiveness of the program, a test was developed to determine the extent to which students activated the training program according to technical specifications that were judged by experts in this field. After the process of analyzing and interpreting the results, the results indicated that the training program is effective and achieves the goal of its design in the field of evaluating the quality of students’ individual performance. Islamic Studies students at Sultan Qaboos University.